Quantitative determination of tocopherols in edible vegetable oils using electrochemical ultra-microsensors combined with chemometric tools - Robledo, Sebastian Noel (2013)
We have developed an electroanalytical method to quantify different isomers of tocopherols in edible vegetable oils. The method uses the square wave voltammetry on a carbon fiber disk ultramicroelectrode in benzene/ethanol+0.1 mol L−1H2SO4. Because the oxidation peaks of these natural antioxidants show an important overlapping, we have used two chemometric tools to obtain the multivariate calibration model. One method was the multivariate curve resolution–alternating least square (MCR–ALS), which assumes a linear behavior, i.e., the total signal is the sum of individual signals of components, and another nonlinear method such as artificial neuronal networks (ANNs). From the accuracy and precision analysis between nominal and estimated concentrations by both methods, we could infer that the ANNs method was a good model to quantify tocopherols in edible oil samples. Recovery percentages were between 94% and 99%. In addition, we found a difference of 1.4–6.8% between the total content of tocopherols in edible oil samples and the vitamin E content declared by the manufacturers.